2021
DOI: 10.21203/rs.3.rs-1014537/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic Sequencing Characterizes a Wide Diversity of Viruses in Field Mosquito Samples in Nigeria

Abstract: Mosquito vectors are a tremendous public health threat as one in six diseases worldwide is vector-borne transmitted mainly by mosquitoes. In the last couple of years, there have been active Yellow fever virus (YFV) outbreaks in many settings in Nigeria, and nationwide, entomological surveillance has been a significant effort geared towards understanding these outbreaks. In this study, we used a metagenomic sequencing approach to characterize viruses present in vector samples collected during various outbreaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…aegypti and Ae. albopictus conducted in different geographical areas of the world (Americas, Asia, Africa, Europe, and Australia) [73,107,121,[127][128][129][130][131][132][133][134] have identified that Aedes host a viral community with high diversity. Currently, the available data focus mainly on Ae.…”
Section: Virome In Ae Aegypti and Ae Albopictusmentioning
confidence: 99%
“…aegypti and Ae. albopictus conducted in different geographical areas of the world (Americas, Asia, Africa, Europe, and Australia) [73,107,121,[127][128][129][130][131][132][133][134] have identified that Aedes host a viral community with high diversity. Currently, the available data focus mainly on Ae.…”
Section: Virome In Ae Aegypti and Ae Albopictusmentioning
confidence: 99%